Validitas Perangkat Pembelajaran IPA Berbasis Masalah Bermuatan Karakter - Tirmayasari Tirmayasari; A. Wahab Jufri; Ahmad Harjono (Department of Physics Education, Universitas Mataram, 2019)
The purpose of of this study is to determine the validity of a learning tools of characters-based problem on light and optical concept. This type of research is Research & Development refers to Dick & Carey model which consists of ten stages namely: identify instructional goal, conduct instructional analysis, analyze learner and contexts, write performance objektives, develop assessment, develop intrucsional strategy, develop and select instructional material, design and conduct formative evaluation of instruction, revise instruction, design and conduct summative evaluation. The formative evaluation stage was done by: the validation of the learning tools (syllabus, lesson plan, students worksheets, evaluation instruments) by three experts twice validation. Validation has been carried out by experts using a validity test instrument in the form of a questionnaire. Validity test for syllabus, lesson plan, student worksheet and evaluation instruments get results with very feasible. In conclusion, learning tools of characters-based problem on light and optical concept was feasible to be applied in science learning processes.